2001
DOI: 10.1111/j.1751-0813.2001.tb10709.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short‐term treatment with bumetanide, quinapril and low‐sodium diet on dogs with moderate congestive heart failure

Abstract: This study suggests that the combined treatment with bumetanide, quinapril and low-sodium diet for controlling moderate CHF due to mitral insufficiency in dogs is simple, easy-to-administer and effective in controlling clinical signs and prompting improvement even after short-term treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…32 Enalapril is commonly used, and a few studies have investigated the effect of quinapril in dogs and found a well-tolerated and effective dos- age. 33,34 As expected, both treatments reduced serum ACE activity in the dogs. Quinapril decreased ACE activity significantly more than did enalapril.…”
Section: Discussionmentioning
confidence: 99%
“…32 Enalapril is commonly used, and a few studies have investigated the effect of quinapril in dogs and found a well-tolerated and effective dos- age. 33,34 As expected, both treatments reduced serum ACE activity in the dogs. Quinapril decreased ACE activity significantly more than did enalapril.…”
Section: Discussionmentioning
confidence: 99%
“…In human beings and small animals, ACE inhibitors are usually used for long‐term application (Schon et al., 1994). But a beneficial effect on left ventricular performance in chronic mitral regurgitation could also be seen after a single dose of quinapril in man (Schon et al., 1994) and after short‐term treatment (4 weeks) in dogs (Martinez‐Alcaine et al., 2001). In our study, we used quinapril for 8 weeks and we could also observe significant beneficial effects on systolic cardiac variables as an increased stroke volume and cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…Results of human studies show that the proportion of patients reporting associated adverse effects, caused by generalized vasodilatation, was lower with quinapril than with captopril or enalapril (Frank et al., 1990). In small animal internal medicine, different ACE inhibitors are successful in treating different cardiovascular disorders, such as CHF and mitral valve insufficiency (Morisse and Kersten, 1995; Martinez‐Alcaine et al., 2001), but there are no studies or literature about the use and effects of ACE inhibitors in horses with mitral valve insufficiencies. Mitral valve insufficiency is the most common cardiovascular disease in horses (Reef et al., 1998) and can lead to exercise intolerance and resulting in acute congestive heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies carried out with ACE1 in veterinary medicine demonstrate the capacity of these drugs to improve, even reverse, lung oedema because of their venous vasodilator and diuretic effects (Kittleson, 2000;Martinez-Alcaine et al, 2001). Similarly 14 dogs had vena cava distension before treatment and only 6 after treatment.…”
Section: Resultsmentioning
confidence: 99%